2014
DOI: 10.5898/jhri.3.1.sabanovic
|View full text |Cite
|
Sign up to set email alerts
|

Designing Robots in the Wild: In situ Prototype Evaluation for a Break Management Robot

Abstract: As robots move into everyday environments, we need to understand both the social and the technical constraints and affordances for human-robot interaction. We use in situ evaluation of partially functioning prototypes to inform the design of robotic technologies that fit their intended contexts of use and illustrate this method through a case study of iteratively designing a desktop robot for break management in a computerized office. After an initial exploratory study of the office as context of use, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…These kinds of studies entail methodological challenges on how to collect the data in the participants' homes. Questionnaires, interviews, sensor and robot logs are usually used [57]. Sensor and data logs are perceived as objective ways of collecting data, since they do not involve researchers invading the homes of the participants.…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of studies entail methodological challenges on how to collect the data in the participants' homes. Questionnaires, interviews, sensor and robot logs are usually used [57]. Sensor and data logs are perceived as objective ways of collecting data, since they do not involve researchers invading the homes of the participants.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a key role is played by the prototyping actions. From low-fidelity to high-fidelity prototypes, tangible artifacts, which appear or behave as desired, allow fast testing and iterations, as reported by Šabanović et al [23]. Finally, usability testing represents another common action in the design of novel robots.…”
Section: The Role Of Design Researchmentioning
confidence: 96%
“…Vázquez et al found that not only a copy of human orientation behavior (attentive orientation) but also an optimized orientation (middle orientation) can be an effective starting point for robot orientation behavior [73]. Sabanovic, Reeder, and Kechavarzi have shown that social behavior, not copied from humans, was preferred over alarm type behavior for minimalistic desk robots [66]. However, guidelines and approaches on how such behaviors should be designed, to our knowledge are scarce.…”
Section: Design Of Humanoid and Non-human-like Robots And Their Behaviormentioning
confidence: 99%